3-DIMENSIONAL ANALYSIS OF THE STRESS-STRAIN RELATION DURING ORTHODONTIC ANCHORAGE ON DENTAL IMPLANTS - Mihai A. Niculescu; Cătălin Popescu; Dan Păunescu (Romanian Society of Oral Rehabilitation, 2015)
This study uses the Finite Element Analysis (FEA) to investigate the stress-strain relation in peri-implant bone, caused by orthodontic anchorage. Materials and method. A tridimensional (3D) mathematical model was created to simulate the frontal teeth distalisation during anchorage on three dental implants. Using FEA was calculated the distribution of equivalent von-Mises stress when orthodontic forces of 2, 3 and 4 N were applied. ANSYS v11 software was properly configured for strain analysis in the model using FEA. Results and discussion. Periradicular maximum equivalent von-Mises stress values were 4,54 MPa for 2 N force, 6,82 MPa for 3 N force and 9 MPa when 4 N force was applied. Conclusions. FEA is a calculation method widely used in structural analysis that proved successfully in medical research. The forces caused by implant anchorage caused peri-implant bone stress in the model. The values of this stress correlated with the criterion of bone remodeling caused by mechanical load, and relative to study conditions, did not revealed biomechanical overload of periimplant bone structure